Alike in many ways: Intergenerational and sibling correlations of brothers' earnings - Paul Bingley; Lorenzo Cappellari (Center for Economic Studies and ifo Institute (CESifo), 2012)
We model the correlations of brothers' life-cycle earnings separating for the first time the effect of paternal earnings from additional residual sibling effects. We identify the two effects by analysing sibling correlations and intergenerational correlations jointly within a unified framework. Our multi-person model of earnings dynamics distinguishes permanent earnings from transitory -serially correlated-shocks, allows for life-cycle effects and nests the models of previous research that have focussed either on intergenerational or sibling correlations. Using data on the Danish population of father/first-son/second-son triplets we find that sibling effects explain between one fourth and one half of inequality in life-cycle earnings, and largely account for individual differences in earnings growth. Intergenerational associations account for a considerable share of overall sibling correlations, between 30 and 60 per cent from youth to maturity. We also find that transitory shocks are correlated across family members, in particular between brothers. Extensions of the model show a distinctive effect of mothers' human capital on top of fathers' earnings and no evidence of differential intergenerational transmission between brothers.
Keywords: D31; J62; 330; intergenerational transmission; sibling correlations; life-cycle earnings